Analysis of the vibration of risers considering coupled longitudinal and transversal displacements and a new numerical approach - Kawano, Alexandre; Zine, Abdelmalek; Morooka, Celso; Ichchou, Mohamed (Ocean engineering, 2021)
The aim of this work is twofold. We analyze a dynamical model for the transversal motion of a vertical riser, which is a long tube used in the petroleum industry for subsea well drilling operations, and in other cases to bring the oil from the bottom to the sea surface. After the analysis, we propose a new numerical approach to solve the resulting system of coupled differential equations. The proposed model, in which transversal displacements are coupled with longitudinal ones, is analyzed from a mathematical point of view, where we proved the existence, and uniqueness for the resulting system of differential equations. A numerical model based on finite element method is discussed and successfully implemented in a Matlab code. The numerical results are compared to those obtained by a commercial computation code ORCAFLEX (Orcina, 2014) and also the experiments. In both situations, the obtained results are very satisfactory and encouraging. AMS (MOS) subject classification 74K10 74H20 74H25 74H45 65N30. •The mathematical model is properly analyzed, considering existence and uniqueness for the resulting system of differential equations.•A numerical model based on finite element method implemented, and the numerical results are compared to those obtained by a commercial code ORCAFLEX.•The FEM results and those obtained by ORCAFLEX are compared with experimental results.•A new computational efficient algorithm based on the finite element method is proposed to simulate the dynamical behavior of a riser.